Indel mutations of sheep PLAG1 gene and their associations with growth traits. Issue 7 (12th December 2022) - Pan, Yun; Wang, Min; Wu, Hui; Akhatayeva, Zhanerke; Lan, Xianyong; Fei, Panfeng; Mao, Cui; Jiang, Fugui
Abstract: Pleiomorphic adenoma gene 1 (PLAG1) is mainly expressed in embryonic development, and it is reported to take an effect on the growth performance of mice, cattle, pigs, and sheep. To explore how conservative the PLAG1 is in different sheep breeds, the effects of the two indel variants on the growth traits of the Chinese Luxi blackhead (LXBH) sheep were firstly detected. The P2-del 30 bp and P4-del 45 bp indel loci of the sheep PLAG1 gene were significantly related to 15 growth traits ( P  < 0.05). Genotype ID and genotype II were dominant for the P2-del 30 bp and P4-del 45 bp loci, respectively. The above findings indicated that the two indel mutations in the ovine PLAG1 gene were suggested to become the molecular markers for the selection of economic traits in sheep.